Using counterfactuals to display facts – the case of satirical humor - Adi Maslo (ExELL (Explorations in English Language and Linguistics))
Satire has not been given the humorologists’ attention to an extent that would do justice to the amount of humor satire actually holds. Therefore, the intention of this paper is to shed light on satire as humorous discourse, with an emphasis on counterfactuals. Interestingly enough, counterfactuals oppose the actual state of affairs; rhetorically however, they show potential to reveal the truth. Political satire is an area of conflict between truth and falsehood which is exactly why this type of satire is discussed in this paper. Tools from Cognitive Linguistics – framing and blending – are utilized to show to what extent counterfactuals are actually false and how they essentially contribute to satire. Examples of political satire are selected from Comedy Central’s The Daily Show.